Critical Points of Vitamin C Production and Long-Acting Pharmaceutical Preparations - Asyfa Fauzia Tiara Putri; Laksmia, Farika Dyani; Salama, Anisa Rakhmania (Halal Center ITS, 2024)
Vitamin C offers numerous benefits, including its role in the immune system. This factor necessitates the intake of exogenous vitamin C because the human body cannot synthesize it endogenously. Long-acting drugs are known to provide long-term therapeutic effects. The halal and haram aspects of Islam are of great importance because of the potential doubt or syubhat between the two. There are different methods for producing vitamin C, such as Reichstein's method or classical two-step fermentation. Generally, vitamin C synthesis involves biotransformation by microorganisms. One approach to creating long-acting preparations is to coat them with gelatin. A product's halal or haram status is determined by its raw materials, additives, and manufacturing processes. Vitamin C production typically involves fermentation using microorganisms; therefore, a halal growth medium must be considered. Long-acting vitamin C preparations that use gelatin should also be evaluated for halal status. If gelatin originates from halal animals, the law depends on the production process. However, if gelatin comes from haram animals, the law is haram.